2014
DOI: 10.1007/s00192-013-2302-9
|View full text |Cite
|
Sign up to set email alerts
|

Climbing a long hill: pelvic floor surgery and the need for geriatric urogynecology

Abstract: The topic of geriatric urogynecology is receiving much attention lately as a public health priority because of the global increase in female life expectancy and the significant risk of associated pelvic floor dysfunctions. Statistics from the USA project that in 2050, 25 % of the population will be >60 years and that those >85 will increase from a population of 1.9 % in 2010 to 4.3 % in 2050 [1]. The urogynecological community should thus expect to face a worldwide and progressively growing demand from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The post-operative morbidity was higher than that in the younger control group as shown by the comparison of complications of the groups CD II and CD III requiring treatment. This corresponds to the observations of other groups [24,28]. In a large retrospective cohort study with over 250 000 patients Sung et al found a 1.4-fold elevated risk for perioperative complications in patients aged 80 years or more [24] on comparison with younger patients.…”
Section: Co-morbidity Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…The post-operative morbidity was higher than that in the younger control group as shown by the comparison of complications of the groups CD II and CD III requiring treatment. This corresponds to the observations of other groups [24,28]. In a large retrospective cohort study with over 250 000 patients Sung et al found a 1.4-fold elevated risk for perioperative complications in patients aged 80 years or more [24] on comparison with younger patients.…”
Section: Co-morbidity Analysissupporting
confidence: 86%
“…No wound infections with problem-causing pathogens were observed in our examined cohorts. Although it is known that advanced age represents an independent risk factor for surgical complications [26], age alone should not be a contraindication for surgical therapy [26,28]. It has been observed in clinical trials that the type and number of co-morbidities determine the risk for surgical complications in elderly female patients.…”
Section: Co-morbidity Analysismentioning
confidence: 99%
“…Vaginal route is preferable for pelvic reconstructive surgery in geriatric patients, as it usually takes shorter operating time and can be performed under regional anaesthesia [4]. Obliterative vaginal procedures are a good option for elderly patients who cannot tolerate extensive surgery and who are not planning future sexual activity [6].…”
Section: Discussionmentioning
confidence: 99%